Mental Health of Nursing Students amid Coronavirus Disease 2019 Pandemic - Gao, Juan; Wang, Fengyun; Guo, Shengcun; Hu, Fudong (Frontiers in Psychology, 2021)
The COVID-19 pandemic is a global disaster, and recent studies have shown its association with increasing mental health problems such as post-traumatic stress disorder (PTSD), depression, anxiety, and stress. Nursing students especially nursing interns may be shunned, harassed, even blamed as potential COVID-19 spreaders, though they were important reserve force against COVID-19 and other diseases. Of note, the psychological influences of COVID-19 on nursing students remained unclear. The aim of this study was to evaluate the mental health of nursing students during the COVID-19 pandemic. A cross-sectional online survey was conducted on nursing students in a vocational college from 12 April 2020 until 23 April 2020. The Impact of Event Scale–Revised, 21-item Depression, Anxiety and Stress Scale, and Pittsburgh Sleep Quality Index were used to assess the degree of symptoms of PTSD, depression, anxiety, stress, and insomnia, respectively. Multivariable logistic regression analysis was performed to determine potential risk factors for psychological symptoms. 1780 college nursing students were asked to participate in this online survey, with 1532 complete responses. In total, 682 (44.5%) college nursing students reported having PTSD, 358 (22.8%) students reported insomnia, but few students reported depression (n=45, 2.9%), anxiety (n=44, 2.9%), and stress (n=17, 1.1%) symptoms. As compared with junior, female, and rural nursing students, respectively, the senior, male, and urban nursing students had higher rates of PTSD, depression, anxiety, stress, while male nursing students had a higher insomnia rate. Multivariable analysis showed that senior nursing students had higher risks of PTSD, depression, anxiety; being male was associated with higher risks of PTSD, depression, anxiety, stress, and insomnia; and urban nursing students had higher risks of PTSD, depression, anxiety, and stress. In summary, a considerable number of nursing students reported mental symptoms of PTSD and insomnia, though few reported mental symptoms of depression, anxiety, and stress. Furthermore, senior, male, and urban nursing students are at risk for developing mental symptoms. Appropriate psychological interventions should be implemented to assure the mental health of nursing students.